2015
DOI: 10.3174/ajnr.a4223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Virtual Noncontrast Images Obtained from Dual-Energy CTA for Diagnosing Subarachnoid Hemorrhage

Abstract: BACKGROUND AND PURPOSE:The virtual noncontrast images generated with iodine subtraction from dual-energy CTA images are expected to replace the true noncontrast images for radiation-dose reduction. This study assessed the feasibility of virtual noncontrast images for diagnosing SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
2
16
0
2
Order By: Relevance
“…Nevertheless, modern CT imaging concepts aim for a reduction of radiation dose without losing essential image information. If VNC images will turn out to be equally robust and potentially able to replace TNC acquisitions, this would result in a considerable radiation dose reduction as already suggested by Jiang et al 15 Our study supports this notion because discarding the TNC image acquisition would have resulted in a mean radiation dose reduction of more than 61 mGy. Furthermore, most relevant findings from TNC images, for example, extent of infarct demarcation or possible underlying neoplastic conditions, can also be detected in commonly acquired late-phase (venous phase) head CT, which is commonly performed after TNC and CTA image acquisitions using approximately the same radiation dose as TNC scans.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, modern CT imaging concepts aim for a reduction of radiation dose without losing essential image information. If VNC images will turn out to be equally robust and potentially able to replace TNC acquisitions, this would result in a considerable radiation dose reduction as already suggested by Jiang et al 15 Our study supports this notion because discarding the TNC image acquisition would have resulted in a mean radiation dose reduction of more than 61 mGy. Furthermore, most relevant findings from TNC images, for example, extent of infarct demarcation or possible underlying neoplastic conditions, can also be detected in commonly acquired late-phase (venous phase) head CT, which is commonly performed after TNC and CTA image acquisitions using approximately the same radiation dose as TNC scans.…”
Section: Discussionsupporting
confidence: 87%
“…7,32 Hence, absolute HU from VNC images in HAS could be used for clinical prognostic appraisals as suggested by previous studies. 7,33 Jiang et al 15 stated that the image quality of VNC images generated from DECT angiography is characterized by a higher image noise level and markedly reduced contrast between gray and white matter compared with TNC images. This might result in a compromised discrimination of subtle signs of infarct demarcation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VNC images have the potential to reduce the patient's radiation exposure by eliminating the need to separately acquire precontrast CT images; however, image quality has been a concern. Although a decrease in the image quality of VNC images, as compared with that of standard nonenhanced CT images, has been reported and has raised concern about the detection of subtle foci of subarachnoid hemorrhage, statistically significant diagnostic inferiority has not been demonstrated (20)(21)(22)(23).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Previous studies have investigated the feasibility of using VUE images in place of TUE images for patients with gastric tumors, resulting in a dose reduction of 30.5%, and in the diagnosis of patients with subarachnoid haemorrhage. 14,15 For imaging of renal lesions, it has been shown that a threshold of 2 mg/cm 3 is the most accurate in distinguishing enhancing from nonenhancing lesions using iodine density images generated from DECT. 16 Other studies have investigated the feasibility of replacing precontrast images with virtual noncontrast images in renal DECT exams.…”
mentioning
confidence: 99%